Perceived health implications of female genital mutilation on women in Ibadan, Oyo state (2020)
Female genital mutilation (FGM) is still practised in Nigeria despite its adverse effects on the emotional, psychological and reproductive wellbeing of women. Studies have focused on prevalence and attitude towards FGM, with negligible attention on its implications on women’s health. The study, therefore, examined the perceived health implications of FGM on women in Ibadan. A cross-sectional survey of 400 randomly selected respondents was conducted to elicit information on reasons for practising FGM, procedures for sterilizing instruments for circumcision and the health implications. Qualitative data were elicited from 8 ln-Depth Interviews (IDIs) with 4 married and unmarried circumcised females and 6 Key Informant Interviews (KIIs) with 2 doctors, nurses and traditional circumcisers each. Quantitative data were analyzed using the statistical package for social sciences (SPSS) and presented using descriptive statistics (frequencies and percentages) and bar charts, while qualitative data were content analyzed. Findings revealed that FGM was practiced mainly for cultural reasons (82.6%), to keep women's virginity (33.1%), control promiscuity (44.9%) among others. The procedure for sterilizing instruments for circumcision in order to prevent infection, included use of methylated spirit (4.3%>), washing with hot water (11.8%) and treating with anti-bacterial substance (1.5%). The poor hygiene practice and sterilization in the procedures of FGM negatively affected the health of circumcised females who sometimes came down with infection and other reproductive health problems. Thus, the practice of FGM has adverse implications for women’s health and, therefore, requires that women be more informed, enlightened and empowered to resist FGM and avert the consequences.